The Relationship Between Online Socialization and Online Social Identity - Işıl Avşar Arık; Birsen Şahin Kütük (Journal of Economy Culture and Society)
Social identity is the part of an individual's self-perception of membership in a social group and it develops through the socialization process. People interact with many different socialization agents such as family, school, friends, mass media, work, and professional groups. In the twenty-first century, socialization has not been able to escape the influence of digital technologies, and they have been considered an alternative to traditional socialization channels. Web 2.0 technologies have become an essential source of online socialization. However, the question of whether online socialization (OS) impacts the formation of online social identities (OSI) is quite limited in the literature. Therefore, this study examined the effects of internet addiction (IA) and the average time spent on social media (ATSM) (as online socialization) on OSI, and the mediate effect of the time spent on the internet when young people are together with their family members (TSIWTF). A quantitative method was used, and data were collected from 272 university students. According to the study results, there is a relationship between OS and OSI, and TSIWTF partly mediates this relation.